2021
DOI: 10.1177/2333794x20981548
|View full text |Cite|
|
Sign up to set email alerts
|

Tuberculosis in Pediatric Solid Organ and Hematopoietic Stem Cell Recipients

Abstract: Children undergoing solid organ and hematopoietic stem cell transplantation are at high risk of morbidity and mortality from tuberculosis (TB) disease in the post-transplant period. Treatment of TB infection and disease in the post-transplant setting is complicated by immunosuppression and drug interactions. There are limited data that address the unique challenges for the management of TB in the pediatric transplant population. This review presents the current understanding of the epidemiology, clinical prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(233 reference statements)
0
1
0
Order By: Relevance
“…In such places, tuberculosis is predominantly because of the reactivation of latent infection. 16 In the United States, studies have shown the incidence of mycobacterial infections in HSCT recipients to be anywhere from 0.0014% to 3%. 17…”
Section: Type Of Infectionsmentioning
confidence: 99%
“…In such places, tuberculosis is predominantly because of the reactivation of latent infection. 16 In the United States, studies have shown the incidence of mycobacterial infections in HSCT recipients to be anywhere from 0.0014% to 3%. 17…”
Section: Type Of Infectionsmentioning
confidence: 99%